Usefulness of the Parameters of Quantitative Myocardial Perfusion Contrast Echocardiography in Patients with Chronic Total Occlusion and Collateral Flow. Issue 3 (28th June 2014) - Cho, Jung Sun; Her, Sung‐Ho; Youn, Ho‐Joong; Kim, Chan Joon; Park, Mahn‐Won; Kim, Gee Hee; Chung, Woo‐Baek; Park, Chan Seok; Cho, Eun‐Joo; Kim, Mi‐Jeong; Jung, Hae‐Ok; Jeon, Hui‐Kyung
<x xml:space="preserve">Abstract</x> Background Microvascular obstruction becomes more severe with longer duration of ischemia, such as chronic total occlusion (CTO) which used to have collateral flow. In this study, we explored the correlation between parameters measured using quantitative myocardial perfusion contrast echocardiography (MCE) and the angiographic collateral flow grades in patients with CTO. Furthermore, we investigated the usefulness of the parameters of quantitative MCE for the measurement of microvasculature changes after revascularization of CTO lesions. Methods Between January 2011 and January 2013, 44 patients who had undergone coronary angiography (CAG) due to chest pain and had confirmed CTO lesions were enrolled in this prospective observational study. All patients had baseline MCE within 24 hours after diagnostic CAG. Patients were then assigned to one of two groups: a medical therapy group (Group I, n = 20) or a reperfusion group with percutaneous coronary intervention (PCI) (Group II, n = 24). All patients had follow‐up MCE 3 months later. Results Consistent with the CAG results in both groups, on baseline MCE, the myocardial blood flow (AI × β) values were higher in Grade III collateral flow than in Grade I or II collateral flow (AI of collateral flow Grade I vs. Grade II vs. Grade III: 2.34 ± 2.65 vs. 2.52 ± 2.67 vs. 3.87 ± 4.57, P = 0.038). The plateau acoustic intensity (AI) and wall‐motion score index (WMSI) were significantly improved at the 3‐month follow‐up after successful reperfusion with PCI (5.75 ± 3.52 before vs. 8.11 ± 6.02 after, P = 0.004) and (1.76 ± 0.83 before vs. 1.43 ± 0.64 after, P ≤ 0.001), respectively. However, the AI and WMSI values were not improved in the medical treatment group, (6.04 ± 4.64 before vs. 6.01 ± 5.52 after, P = 0.966) and (1.61 ± 0.82 before vs. 1.66 ± 0.67 after, P = 0.616), respectively. Conclusions MCE is a useful tool for estimating microvascularity in patients with CTO lesions and correlates well with angiographic collateral flow.